2023
DOI: 10.1111/cns.14095
|View full text |Cite
|
Sign up to set email alerts
|

PERK‐STING‐RIPK3 pathway facilitates cognitive impairment by inducing neuronal necroptosis in sepsis‐associated encephalopathy

Abstract: Aims Sepsis‐associated encephalopathy (SAE) is a common but serious complication in septic survivors and often causes long‐term cognitive impairments. The role of RIPK3‐participated necroptosis in SAE remains obscured. STING is a key molecule in regulating necroptosis and apoptosis. However, there is uncertainty as to the mechanisms of STING in CLP‐induced SAE. The aim of this study was to investigate whether STING is involved in the underlying mechanism of SAE. Methods The contextual fear conditioning test (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“… 114 Additionally, the ER stress-related protein PERK induces necroptosis through the stimulator of interferon genes-mediated RIPK3 signaling pathway. 115 Moreover, the RIPK3/CaMKII signaling pathway axis may also mediate ERS-induced necroptosis, although the specific mechanisms remain unexplored. 116 However, cell necroptosis in the heart is not directly associated with RIPK1/RIPK3/MLKL signaling.…”
Section: Upr-mediated Cell Deathmentioning
confidence: 99%
“… 114 Additionally, the ER stress-related protein PERK induces necroptosis through the stimulator of interferon genes-mediated RIPK3 signaling pathway. 115 Moreover, the RIPK3/CaMKII signaling pathway axis may also mediate ERS-induced necroptosis, although the specific mechanisms remain unexplored. 116 However, cell necroptosis in the heart is not directly associated with RIPK1/RIPK3/MLKL signaling.…”
Section: Upr-mediated Cell Deathmentioning
confidence: 99%
“…Investigation into the trends of PERK, STING, and RIPK3 (serine/threonine protein kinase 3) in the hippocampal tissues of SAE mice revealed that STING may inhibit neuronal necrosis through the RIPK3 pathway, thereby potentially preventing neuronal necrotic apoptosis and enhancing cognitive function. 79 Currently, research on the cGAS-STING signaling pathway in septic encephalopathy development remains in its early stages, having only initially revealed the correlation between STING and septic encephalopathy. Further experimental and clinical studies are required to validate these relationships more comprehensively.…”
Section: Organ Tissue Damage Caused By Activation Of Cgas-sting Signa...mentioning
confidence: 99%
“…Studies have demonstrated that innate immunity can concurrently regulate pyroptosis, apoptosis, and necroptosis through the PANoptosome complex, in which Z-DNA binding protein 1 (ZBP1) with Zα molecules is crucial ( 39 ). The cGAS-STING pathway, a constituent of the innate immune system, can initiate various forms of RCD, such as pyroptosis, apoptosis, and necroptosis, suggesting that the cGAS-STING pathway may regulate PANoptosis ( 22 , 56 , 181 , 182 ). Additionally, a comprehensive analysis has verified the occurrence of PANoptosis in ischemic brain injury, indicating its potential as a therapeutic target ( 183 ).…”
Section: Role Of Cgas-sting Pathway In Pathophysiology Of Ischemic St...mentioning
confidence: 99%
“…The subsequent release of various DAMPs triggers an innate immune response ( 194 ). A study on sepsis-associated encephalopathy indicated that STING expression in hippocampal neurons is elevated and interacts with PERK, a significant factor of ER stress, to promote p-RIPK3/RIPK3 expression in damaged neurons ( 181 ). This suggests that modulation of the PERK-STING-RIPK3 pathway may have neuroprotective effects by reducing neuroinflammation.…”
Section: Role Of Cgas-sting Pathway In Pathophysiology Of Ischemic St...mentioning
confidence: 99%